Management and outcome of bleeding pseudoaneurysm associated with chronic pancreatitis - Jan Yi-Yin; Hwang Tsann-Long; Chen Han-Ming; Hung Chien-Fu; Yeh Chun-Nan; Hsu Jun-Te; Chen Miin-Fu (BMC Gastroenterology, 2006)
Abstract Background A bleeding pseudoaneurysm in patients with chronic pancreatitis is a rare and potentially lethal complication. Optimal treatment of bleeding peripancreatic pseudoaneurysm remains controversial. This study reports on experience at Chang Gung Memorial Hospital (CGMH) in managing of bleeding pseudoaneurysms associated with chronic pancreatitis. Methods The medical records of 9 patients (8 males and 1 female; age range, 28 – 71 years; median, 36 years) with bleeding pseudoaneurysms associated with chronic pancreatitis treated at CGMH between Aug. 1992 and Sep. 2004 were retrospectively reviewed. Alcohol abuse (n = 7;78%) was the predominant predisposing factor. Diagnoses of bleeding pseudoaneurysms were based on angiographic (7/7), computed tomographic (4/7), ultrasound (2/5), and surgical (2/2) findings. Whether surgery or angiographic embolization was performed was primarily based on patient clinical condition. Median follow-up was 38 months (range, 4 – 87 months). Results Abdominal computed tomography revealed bleeding pseudoaneurysms in 4 of 7 patients (57%). Angiography determined correct diagnosis in 7 patients (7/7, 100%). The splenic artery was involved in 5 cases, the pancreaticoduodenal artery in 2, the gastroduodenal artery in 1, and the middle colic artery in 1. Initial treatment was emergency (n = 4) or elective (n = 3) surgery in 7 patients and arterial embolization in 2. Rebleeding was detected after initial treatment in 3 patients. Overall, 5 arterial embolizations and 9 surgical interventions were performed; the respective rates of success of these treatments were 20% (1/5) and 89% (8/9). Five patients developed pseudocysts before treatment (n = 3) or following intervention (n = 2). Pseudocyst formation was identified in 2 of the 3 rebleeding patients. Five patients underwent surgical treatment for associated pseudocysts and bleeding did not recur. One patient died from angiography-related complications. Overall mortality rate was 11% (1/9). Surgery-related mortality was 0%. Conclusion Angiography is valuable in localizing bleeding pseudoaneurysms. In this limited series, patients with bleeding pseudoaneurysms associated with chronic pancreatitis treated surgically seemingly obtained good outcomes.